Accessibility evaluation of interaction modalities and cognitive process of self-service technologies’ user interface in Japan - Mäkipää, Juho-Pekka; Iijima, Junichi (Elsevier, 2025)
As more and more services are becoming available only in digital form, self-service technologies (SSTs) need to be accessible to ensure all citizens have equal opportunities to participate in society. However, SSTs’ accessibility is still insufficient, and the overall picture of possible accessibility issues with SSTs is fragmented. In this study, we evaluated the accessibility of a sample of 20 SSTs in Japan by examining variables in user perception and action, factors related to cognitive accessibility, and user interface components. The findings are twofold. First, we illustrated the multimodalities in SST interaction based on the theory of human-computer interaction. Then, we identified SST user interface design practices that impact human cognition. This study illustrates the current reality of how accessibility is actualized and proposes future research directions and practices for the SST industry to develop and improve SSTs’ accessibility.
Keywords: Accessibility; Self-service technologies; Interaction modalities; Cognition; Information Systems Science; Tietojärjestelmätiede